Association of Glycated Hemoglobin Levels with Amputation Outcomes in Patients with Diabetic Foot Ulcers: A Cross-Sectional Study in Southern Iran (2023–2024) - Heidarykhayat, Sahar; Jamali, Kazem; Zaferani Arani, Hamid; Abbasy, Zahra; Niakan, Mohammad Hadi (Galen Medical Journal, 2025)
Background: Diabetic foot ulcer (DFU) is the most serious consequence of type 2 diabetes mellitus (T2DM). Glycated hemoglobin (HbA1c) acts as a marker of long-term glycemic control, but its prognostic value in predicting the severity in DFU patients remains undefined. This study aims to investigate the association between HbA1c levels and lower limb amputation risk at various anatomical levels in patients with DFU. Materials and Methods: This cross-sectional analytical study included 446 patients with T2DM and DFU admitted to Namazi Hospital, Shiraz, Iran, between February 2023 and January 2024. Patients were categorized into four groups based on the amputation level: above-knee, below-knee, foot/midfoot/forefoot, and toe/finger. HbA1c was measured and categorized into three groups (7–7.9%, 8–8.9%, and ≥9%). Univariate and multinomial logistic regression analyses were performed using the above-knee amputation group as the reference. Statistical analysis was conducted in R (v4.4.1), with significance set at P < 0.05. Result: Elevated HbA1c levels were significantly associated with increased odds of below-knee and foot amputations compared to above-knee amputation (OR = 6.27, P = 0.023 and OR = 8.16, P = 0.036, respectively, for HbA1c 8–8.9%). Similar associations were observed for HbA1c ≥9%. Additionally, patients who underwent less extensive amputations (i.e., foot and finger) tended to be younger and had shorter hospital stays compared to those who underwent above-knee amputations. Lower triglyceride levels were also associated with finger amputation (OR = 0.99, p = 0.031). These comparisons were made within all patients which had diabetic foot ulcers. Conclusion: Higher HbA1c levels are significantly associated with more distal amputation levels in patients with DFU. Patient characteristics such as younger age, shorter hospitalization, and lower triglyceride levels were more common among those undergoing less extensive amputations. These findings highlight the need for early glycemic control in DFU patients at risk of limb loss.